DETERMINING THE OPTIMAL CAPITAL STRUCTURE OF TELECOMMUNICATION MANUFACTURER COMPANY (A CASE STUDY OF PT XYZ) - Felynda, Afilia
Indonesia is still relatively lagging in implementing an inclusive internet when compared to several neighboring countries. The uneven digital access is caused by planning and data collecting issues due to a lack of cooperation between the central and local governments in building telecommunications networks. As a result, the government is attempting to continue developing and equalizing communications infrastructure since equitable access is critical in satisfying the rights of all Indonesians. One of the most needed telecommunication infrastructures currently is the construction and development of Base Transceiver Stations (BTS) in areas that still lack a network.